Child Welfare, Juvenile Justice, Mental Health, and Education Providers' Conceptualizations of Trauma-Informed Practice. (May 2016) - Donisch, Katelyn; Bray, Chris; Gewirtz, Abigail
This study systematically examined child-service providers' conceptualizations of trauma-informed practice (TIP) across service systems, including child welfare, juvenile justice, mental health, and education. Eleven focus groups and nine individual interviews were conducted, totaling 126 child-service providers. Conventional content analysis was used to analyze the qualitative data with interrater reliability analyses indicating near perfect agreement between coders. Qualitative analysis revealed that child-service providers identified traumatic stress as an important common theme among children and families served as well as the interest in TIP in their service systems. At the same time, child-service providers generally felt knowledgeable about what they define TIP to be, although they articulated wide variations in the degree to which they are taught skills and strategies to respond to their traumatized clients. The results of this study suggest a need for a common lexicon and metric with which to advance TIP within and across child-service systems.